PENERAPAN METODE ACTIVITY BASED MANAGEMENT GUNA MENINGKATKAN EFISIENSI SUMBER DAYA PADA BISNIS KULINER AYAM BAKAR WONG SOLO DI KOTA MALANG - Sri Rahayu; Abdul Wahid Mahsuni; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2022)
The activity-Based Management (ABM) method is one of the activity management methods that aim to increase customer value and generate profits. ABM is a concept to know if the company uses its resources. This study aims to determine the application of the Activity-Based Management (ABM) method to the Business of the Wong Solo Grilled Chicken Business. The type of research conducted by the author in this study is qualitative with a case study approach. The data analysis process includes data reduction, data presentation, conclusions, or verification. The results showed that the three non-value added activities could be eliminated or merged with other or previous activities. In this case, it can be assumed that the daily production cost is Rp. 2,000,000 x 7.5% water requirement = Rp. 150.000.-. So that it can save water needs (electricity costs, because it uses ground water) in one process of Rp. 150.000,-.Keywords: Activity-Based Management, Resource Efficiency